New insights into the ~74 ka Toba eruption from sulfur isotopes of polar ice cores - Crick, Laura; Burke, Andrea; Hutchison, William; Kohno, Mika; Moore, Kathryn A.; Savarino, Joel; Doyle, Emily A.; Mahony, Sue; Kipfstuhl, Sepp; Rae, James W. B.; Steele, Robert C. J.; Sparks, R. Stephen J.; et al. (Climate of the Past, 2021)
LC is funded by the University of St Andrews St Leonards 7th Century Scholarship (-117THCENT01) in partnership with the IAPETUS Natural Environment Research Council Doctoral Training Partnership. AB is funded by a European Research Council (ERC) Marie Curie Career Integration Grant (CIG14-631752) and NERC Strategic Environmental Science Capital Call (CC082). WH is funded by a UKRI Future Leaders Fellowship (MR/S033505/1). MK was funded through DFG-Project Wo 362 /32-1 and Wo 362/46-1,2 to G. Wörner at GZG, University Göttingen. RSJS is funded by a Leverhulme Grant (RPG-2015-246) and Leverhulme Emeritus Fellowship (EM-2018-050) and EWW is funded by a Royal Society Professorship. The ∼74 ka Toba eruption was one of the largest volcanic events of the Quaternary. There is much interest in determining the impact of such a large event, particularly on the climate and hominid populations at the time. Although the Toba eruption has been identified in both land and marine archives as the Youngest Toba Tuff, its precise place in the ice core record is ambiguous. Several volcanic sulfate signals have been identified in both Antarctic and Greenland ice cores and span the Toba eruption 40Ar/39Ar age uncertainty. Here, we measure sulfur isotope compositions in Antarctic ice samples from the Dome C (EDC) and Dronning Maud Land (EDML) ice cores at high temporal resolution across 11 of these potential Toba sulfate peaks to identify candidates with sulfur mass-independent fractionation (S-MIF), indicative of an eruption whose plume reached altitudes at or above the stratospheric ozone layer. Using this method, we identify several candidate sulfate peaks that contain stratospheric sulfur. We further narrow down potential candidates based on the isotope signatures by identifying sulfate peaks that are due to a volcanic event at tropical latitudes. In one of these sulfate peaks at 73.67 ka, we find the largest ever reported magnitude of S-MIF in volcanic sulfate in polar ice, with a Δ33S value of −4.75 ‰. As there is a positive ...